SPESIES UNGGUL Trichoderma Spp INDIGENUS RIZOZFIR PISANG SEBAGAI PENGENDALI PENYAKIT LAYU Fussarium PADA BIBIT TANAMAN PISANG MAS HASIL KULTUR IN VITRO - Anis Shofiyani; Gayuh Prasetyo Budi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
This research will be attempts to obtain strain superior Trichoderma that had ability to colonize roots in mas cultivar banana seedlings so that expected can induce resistant plants to the attack fungi Fusarium oxysporum f.sp . the cause of the disease wither in banana crop result in vitro cultures.Research carried out in the Green House Agricultural Faculty, University of Muhammadiyah Purwokerto, time or carried out 8 months. A design that is a Random Block Design treatment which were examined consists of 2 factor of treatment that is for biological agent antagonist Trichoderma sp, consisting of 2 species that is Trichorderma harzianum (T1), and Trichorderma viride (T2 processor). The second treatment is a way to Trichoderma application that consists of two that is, by immersion banana into the suspension Trichoderma (P1) and the sprinkling planting medium to isolate Trichoderma spp (P2). All organised in factorial with three replications, and each unit treatment uses 10 plants that will use 40 polybags. The result showed that application biological agent Trichoderma (T. Harzianum and T viride) during the research proved an emphasis on the attack disease Fussarium in seed, was shown to the low disease severity attacks. For biologist agenues and biodiversity Trichoderma ( T. Harzianum and T. Viride) which is applied by immersion and the sprinkling can have an influence on the increase of leaves in seeds during the research, and have no effect on than plants and diameter in each stem treatment. However, it is a gift Trichoderma growth able to give a better than without treatment Trichoderma (control) and proved to be able to colonize banana seedlings root is endofit in banana mas seedling result in vitro culture. Keywords: Fusarium, Trichoderma, Biological control Technology